Study on dynamic and static load characteristics and rockburst induced mechanism under the influence of fault - Anying Yuan; Peng Kong; Pu Wang; Chang Liu; Li Lu (Scientific Reports)
Abstract The fault slip type rockburst has the characteristics of large impact range, strong suddenness, and severe impact manifestation. Its influencing factors are numerous; the triggering mechanism is complex, so it seriously threatens the safety production of coal mines. This article adopts the method of numerical simulation to Liang Baoshi Coal Mine 3301 working face mining thick coal seam through fault as engineering background, based on the dynamic analysis module, put forward the “fault formation - mining induced fault slip - dynamic response of stope” whole process numerical simulation method, carry out the fault affected zone of dynamic and static load characteristics and mechanism of rockburst induced is studied. Research shows that: the normal fault fracture zone of surrounding rock stress value is generally lower, but outside the fault fracture zone, there is a stress increase area of about 140 m in the hanging wall and footwall, and the stress concentration factor of footwall is higher which reaches 1.33. In the process of mining of the working face, the advanced abutment stress and the structural stress near the fault are superimposed, and the surrounding rock of the stope formed a large-scale and high static load stress environment. When the working face advancing to fault location, fault slip release form of seismic moment (M0) exponentially increase, the dynamic disturbance stress caused by the fault slip induced the instability and failure of roadway in high static load area in a very short time. The research results provide reference for rockburst risk assessment and safe mining design in fault affected zone.